2008
DOI: 10.1073/pnas.0801329105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced contextual fear memory in central serotonin-deficient mice

Abstract: Central serotonin (5-HT) dysregulation contributes to the susceptibility for mental disorders, including depression, anxiety, and posttraumatic stress disorder, and learning and memory deficits. We report that the formation of hippocampus-dependent spatial memory is compromised, but the acquisition and retrieval of contextual fear memory are enhanced, in central 5-HT-deficient mice. Genetic deletion of serotonin in the brain was achieved by inactivating Lmx1b selectively in the raphe nuclei of the brainstem, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 53 publications
9
122
1
Order By: Relevance
“…This finding is in agreement with reports in several genetic models of 5-HT-deficient mice (Dai et al, 2008;Kiyasova et al, 2011) and with numerous studies using pharmacological approaches to decrease brain 5-HT in rats (Graeff, 2004;Griebel, 1995). Furthermore, decreased 5-HT input at several receptors (including the 5-HT 2A and 5-HT 2C subtypes) clearly reduces anxiety in mice (Heisler et al, 2007;Mongeau et al, 2010;Weisstaub et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is in agreement with reports in several genetic models of 5-HT-deficient mice (Dai et al, 2008;Kiyasova et al, 2011) and with numerous studies using pharmacological approaches to decrease brain 5-HT in rats (Graeff, 2004;Griebel, 1995). Furthermore, decreased 5-HT input at several receptors (including the 5-HT 2A and 5-HT 2C subtypes) clearly reduces anxiety in mice (Heisler et al, 2007;Mongeau et al, 2010;Weisstaub et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…In the NSF, which involves a conflict between the drive to feed and risk assessment behaviors triggered by the unfamiliar environment, VMAT2 sertÀcre mice showed an anxiolytic-like behavioral profile. This agrees with the anxiolytic-like effect of PCPA-induced 5-HT depletion and with observations in other 5-HT depleted mutant mice (Dai et al, 2008;Kiyasova et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The conditional Lmx1b À/À mice also exhibit some behavioral abnormalities as adults (Dai et al, 2008). They have impaired retrieval of spatial memory, as tested in the Morris water maze.…”
Section: Targeting the Development Of 5-ht Neurons In The Raphementioning
confidence: 99%
“…It has been found that l-tryptophan depresses while levodopa intensifies emotional reactivity, the former lowering the level of endogenous 5-HT. And it was also found that lack of 5-HT enhances the emotional reactivity to learned fear memories [34] . So the major benefit of the 5-HT drug is alleviated anxiety and improved sleep.…”
Section: Serotonin (5-ht) -Unpleasant Markermentioning
confidence: 99%